Ecophysiologie de l'huître creuse Crassostrea gigas (Thunberg) : analyse bioénergétique de la gamétogenèse sous trois conditions trophiques distinctes - Bourles, Yves (2004)
The Pacific oyster (Crassostrea gigas) is a major cultivated shellfish resource in France, which represented a tumover of 220 millions € in 2000. Mass mortalities among this commercially important bivalve species are known in France since about 40 years, but have become a recun'ing obstacle for growers of oysters and a threaten for commercial production along the French Atlantic coast in the last 20 years. Since 2000, IFREMER is canying out a multidisciplinary program, MOREST, ta understand the problem of summer mortality, and possibly ta solve il. As part of the MOREST program, the present study focuses on the relationship between gametogenesis, metabo lism and mortality of 7-month, i.e. juvenil e, C. gigas. In April 2004, a total of 2250 oysters were separated in 3 groups and fed 3 different food concentrations: a poor food level (CNO) which fairly enabled positive growth; a low food level (CN I) which a llowed a moderate growth and a weak gametogenesis; a high food level (CNJ) which promoted both somatic and gonadic growth. From April to July 2004, data about oyster ecophysiology, metaboli sm, histology and biometry were collected on these 3 groups at a regular basis. Results show that the higher the food level is (CN3), the more juvenile oysters invest in gonad development, the more their metabo lic balance ("scope for growth") becomes depressed before fa lling down drastically, and the more the oysters die-off. At CN3, mortality rates reach up to 51 %. At low and poor food levels, gonad development of oysters is slightly positive (CN1) or almost null (CNO), whereas their scope for growth is fairly null and mortality does not exceed 4 and 9 %, respectively for CNO and CN1. Three major stages during gametogenesis may be critical for juvenile oysters: (1 ) a phase of active gametogenes is when juveniles allocate most of their energy to gonad development; (2) when gametogenes is reaches a maximum, while the energetic budget of oysters becomes negative; (3) a final phase whi ch coincides with gamete emission ...